2013
DOI: 10.1590/s1415-47572013000200022
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Melipona scutellaris (Hymenoptera, Apidae, Meliponini) fat body transcriptome

Abstract: The insect fat body is a multifunctional organ analogous to the vertebrate liver. The fat body is involved in the metabolism of juvenile hormone, regulation of environmental stress, production of immunity regulator-like proteins in cells and protein storage. However, very little is known about the molecular mechanisms involved in fat body physiology in stingless bees. In this study, we analyzed the transcriptome of the fat body from the stingless bee Melipona scutellaris. In silico analysis of a set of cDNA li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Subsequently, Marchal et al [33], using the locust Schistocerca gregaria as a model, showed that JHAMT, and not FAMeT, is the enzyme involved in JH synthesis. In the honey bee genome we found orthologs for both, famet and mt genes, and when assaying their expression by means of RT-qPCR we found that mt transcripts were specifically detected in CA-CC complex, whereas famet was transcribed more ubiquitously, as is also the case in the highly eusocial stingless bee Melipona quadrifasciata [34]. This leads us to infer that mt and not famet is the gene encoding a functional methyltransferase activity in the honey bee CA.…”
Section: Discussionmentioning
confidence: 73%
“…Subsequently, Marchal et al [33], using the locust Schistocerca gregaria as a model, showed that JHAMT, and not FAMeT, is the enzyme involved in JH synthesis. In the honey bee genome we found orthologs for both, famet and mt genes, and when assaying their expression by means of RT-qPCR we found that mt transcripts were specifically detected in CA-CC complex, whereas famet was transcribed more ubiquitously, as is also the case in the highly eusocial stingless bee Melipona quadrifasciata [34]. This leads us to infer that mt and not famet is the gene encoding a functional methyltransferase activity in the honey bee CA.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, behavioral studies are important for future management of this threatened stingless bee. We collected two colonies of M. scutellaris in 2007 and started studies of its biology (Sousa et al 2013;Santos et al 2015). We here show that excess virgin queens are killed by workers, a phenomenon triggered by a change in CHC profiles of virgin queens during the first days of their life.…”
Section: Introductionmentioning
confidence: 76%
“…There are few transcripts analyses of fat body published so far, such as Bactocera dorsalis [ 12 ], Melipona scutellaris [ 99 ], and Aedes aegypti [ 100 ], and none are related to triatomines.…”
Section: Resultsmentioning
confidence: 99%